Non-Alcoholic Fatty Liver Disease (NAFLD) in overweight and obese children and adolescents - Ralf Schiel; Mario Heinrichs; Günter Stein; Rolf Bambauer; Antje Steveling (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Over the last decades overweight, obesity and non-alcoholic fatty liver disease (NAFLD) in childhood and adolescence increased. NAFLD is strongly associated with insulin resistance, hypertension, dyslipidemia and other pro-atherogenic conditions. It was the aim of the trial to analyze the prevalence of NAFLD, risk factors and comorbidities in a cohort of overweight and obese children and adolescents.  Patients and methods: Totally 79 children and adolescents with overweight/obesity (age 13.3 ± 2.4 years, BMI 33.4 ± 6.5 kg/m², BMI-SDS 2.72 ± 0.52) participated in a structured treatment and teaching program [STTP] (36.1 ± 5.9 days) for weight reduction were included.  Results: NAFLD was diagnosed in 42/79 (53%) of patients. Patients with NAFLD were older (14.0±2.2 vs 12.5±2.5 years, p=0.005), had a higher BMI (36.8±6.4 vs 29.6±4.1 kg/m², p<0.001), BMI-SDS (2.96±0.48 vs 2.45±0.42, p<0.001) and higher fasting C-peptide (0.77±0.33 vs 0.61±0.28 nmol/l, p=0.018), fasting insulin concentrations (23.4±11.4 vs 15.4±12.1 µIU/ml, p=0.004) and HOMA-index (4.80±2.48 vs 3.22±3.46, p=0.022). Moreover patients with NAFLD had higher values in thickness of A. carotis intima. After an in-patient treatment lasting in the mean 5 weeks children/adolescents reached a mean weight reduction of 3.8±2.7 (range, -15.5-+0.8) kg (p<0.001) along with an improvement of risk parameters. The most important factors associated with NAFLD (R-square=0.444) revealed by the multivariate analysis were: body weight (ß=0.407, p<0.001), HOMA (ß=0.265, p=0.014) and HDL-cholesterol (ß=-0.229, p=0.018) at onset of the trial.  Discussion: Children/adolescents with NAFLD were more likely overweight or obese, had more frequently metabolic risk factors and a higher thickness of A. carotis intima media. The data also suggest an improvement in metabolic and cardiovascular risk factors after a significant weight reduction.